Ajaran Rasul Paulus “Menjadi Serupa dengan Kristus” Ditinjau dari Konsep “meniru” Richard Dawkins - Valeria Sonata (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2023)
This article aims to examine the suitability of the human evolutionary process, as proposed by Richard Dawkins, with the concept of “becoming like Christ,